PENGARUH KEBIJAKAN UTANG, KEBIJAKAN DIVIDEN, DAN RISIKO BISNIS TERHADAP KEPEMILIKAN MANAJERIAL - Satrio Yudhotomo, - (2019)
This research was conducted to examine the effect of debt policy, dividend policy, and business risk on managerial ownership. The study was conducted on Manufacturing Sector Companies listed on the Indonesia Stock Exchange as a sample. The sampling technique uses the purposive sampling method (purposive sampling method). The sample selection of 156 Manufacturing Companies listed on the Indonesia Stock Exchange in 2014-2017 produced 14 acceptable companies. Data analysis was performed using Microsoft Excel 2010 and hypothesis testing in this study used Panel Data Regression Analysis with the E-Views 9.0 program and a significance level of 5%. The results of the test are obtained (1) debt policy stated with DER does not affect managerial ownership, (2) dividend policy stated by the DPR does not affect managerial ownership, (3) business risk expressed by ROE standard deviation does not affect managerial ownership.